Optimization of Cathechin Extraction for Development of Liquid Hand Soap Made From Gambier - Daimon Syukri; Rini Rini; Adhitya Jessica (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2023)
This study has aimed to determine the potential use of catechins derived from gambier as an anti-microbial raw material in the manufacture of hand washing liquid soap. The study started from the purification process of catechins from gambier and continued with the addition of gambier to the soap formula looking for hand washing. In this study, there were some difficulties in obtaining catechin extracts that could dissolve in water due to the character of catechins that did not dissolve completely in water. Therefore, the optimization of the catechin extraction process is optimized first. The catechin extraction process was carried out in two ways, namely by using a homogenizer at a speed of 15000 rpm for 30 minutes and a reflux process with hot water (temperature 70 degrees Celsius) for one hour. It was found that the concentration of catechin dissolved in water both in the homogenizer and reflux results was relatively the same, therefore for the manufacture of hand washing liquid soap, the process with the reflux technique would be recommended because of the cheaper operational costs.